Cow Farmers’ Homes Host More Diverse Airborne Bacterial Communities Than Pig Farmers’ Homes and Suburban Homes - Amin, Hesham; Šantl-Temkiv, Tina; Cramer, Christine; Vestergaard, Ditte V.; Holst, Gitte J.; Elholm, Grethe; Finster, Kai; Bertelsen, Randi J.; Schlünssen, Vivi; Sigsgaard, Torben; Marshall, Ian P. G. (Frontiers in Microbiology, 2022)
Living on a farm has been linked to a lower risk of immunoregulatory disorders such as asthma, allergy, and inflammatory bowel disease. It is hypothesized that a decrease in the diversity and composition of indoor microbial communities is a sensible explanation for the upsurge in immunoregulatory diseases, with airborne bacteria contributing to this protective effect. However, the composition of this potentially beneficial microbial community in various farm and suburban indoor environments is still to be characterized. We collected settled airborne dust from stables and the associated farmers' homes and from suburban homes using electrostatic dust collectors (EDCs) over a period of 14 days. Then qPCR was used to assess bacterial abundance. The V3-V4 region of the bacterial 16S rRNA gene was amplified and sequenced using an Ilumina MiSeq in order to assess microbial diversity. The DADA2 algorithm was used for the inference of amplicon sequence variants from amplicon data. Airborne bacteria were significantly more abundant in farmers' indoor environments than in suburban homes (P < 0.001). Cow farmers’ homes had significantly higher bacterial diversity than pig farmers’ and suburban homes (P < 0.001). Bacterial taxa such as Firmicutes, Prevotellaceae, Lachnospiraceae, and Lactobacillus were significantly more abundant in farmers’ homes than suburban homes, and the same was true for beneficial intestinal bacterial species such as Lactobacillus amylovorus, Eubacterium hallii and Faecalibacterium prausnitzii. Furthermore, we found a higher similarity between bacterial communities in individual farmers’ homes and their associated cow stables than for pig stables. Our findings contribute with important knowledge on bacterial composition, abundance and diversity in different environments which is highly valuable in the discussion on how microbial exposure may contribute to the development of immune-mediated diseases in both children and adults.